2006
DOI: 10.2500/ajr.2006.20.2906
|View full text |Cite
|
Sign up to set email alerts
|

Brain Perfusion Single Photon Emission Computed Tomography Findings in Patients with Posttraumatic Anosmia and Comparison with Radiological Imaging

Abstract: Findings suggest that by using SPECT, posttraumatic anosmia corresponds to the hypoperfusion in the orbital frontal cortex in a great number of patients. Because of its availability, rather low cost, technical ease, and possibility to obtain objective quantitative information, brain perfusion SPECT can be complementary to other diagnostic techniques in the evaluation of olfactory function, although additional neurophysiological and imaging studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
(32 reference statements)
3
18
2
Order By: Relevance
“…These results suggest that olfactory dysfunction decreases cortical responses to trigeminal stimulation. A single-photon emission computed tomography (SPECT) study reported that blood flow abnormality in the frontal lobe (particularly, in the orbitofrontal regions) was commonly observed in the posttraumatic anosmic patients (Eftekhari et al 2006). These previous studies are consistent with the present results in that olfactory dysfunction decreased cortical activities in response to chemical substances.…”
Section: Effects Of Dysosmia On Hemodynamic Responsessupporting
confidence: 91%
“…These results suggest that olfactory dysfunction decreases cortical responses to trigeminal stimulation. A single-photon emission computed tomography (SPECT) study reported that blood flow abnormality in the frontal lobe (particularly, in the orbitofrontal regions) was commonly observed in the posttraumatic anosmic patients (Eftekhari et al 2006). These previous studies are consistent with the present results in that olfactory dysfunction decreased cortical activities in response to chemical substances.…”
Section: Effects Of Dysosmia On Hemodynamic Responsessupporting
confidence: 91%
“…15 In another study conducted by Eftekhari et al , 78% of the posttraumatic anosmic patients had abnormal SPECT findings in their orbital and frontal regions. 14 This result was slightly lower than the one in our study, viz. , 82% MRI abnormality and 85% SPECT abnormality.…”
Section: Discussioncontrasting
confidence: 73%
“…Therefore, certain objective tests such as magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT), positron emission tomography scan, and functional MRI have been proposed as imaging methods. 1216…”
mentioning
confidence: 99%
“…In addition, the aforementioned region was demonstrated on our prior studies that had an important role in status of olfactory. It may amend to do a follow up study in MS patients [ 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%